Visualization of Patriarchal Culture in the Film Kartini (2017): A Semiotic Analysis by John Fiske - Pratiwi, Rizky Indah; Kartika, Bambang Aris; Hartanto, Denny Antyo; Murti, Ghanesya Hari (Journal of Language, Communication, and Tourism, 2024)
Film is a medium that represents various socio-cultural realities, enabling the visualization and depiction of social issues, one of which is the culture of patriarchy. Patriarchy is a term used to describe a social system where power, control, and authority are primarily in the hands of men or male figures. Patriarchy is a central theme in the film Kartini. Therefore, the aim of this study is to reveal and understand the hidden meanings that depict the visualization of patriarchal culture in the film Kartini. This study employs a qualitative research method, utilizing John Fiske's semiotic analysis approach. The findings of this research indicate that patriarchal culture is visualized through John Fiske's three codes of encoding, including 1) reality, 2) representation, and 3) ideology, demonstrating that patriarchal culture remains influential in affecting women's lives.